"To Be an Author" : Letters of Charles W. Chesnutt, 1889-1905 - Chesnutt, Charles W. (Charles Waddell), 1858-1932 (Book collections on Project MUSE., 1997)
Collected in this volume are the 1889--1905 letters of one of the first African-American literary artists to cross the ""color line"" into the de facto segregated American publishing industry of the turn of the century. Selected for inclusion are those chronicling the rise of Charles W. Chesnutt (1858-1932), an attorney and businessman in Cleveland, Ohio, who achieved prominence as a novelist, short story writer, essayist, and lecturer despite the obstacles faced by a man of color during the ""Jim Crow"" period. In his insightful commentaries on his own situation, Chesnutt provides as well